Asosiasi Bakau (Rhizophora apiculata Blume.) dengan Jenis-Jenis Mangrove Lainnya di Pantai Bama Taman Nasional Baluran Jawa Timur - Istomo Istomo; Sandy Ghifary (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2021)
Mangroves’s forest at Bama Beach has 95.8 ha. The purpose of this research is to studied the association of Rhizophora apiculata that lives dominant at Bama Beach Baluran National Park East Java. The methods used in data collection is an analytical method of vegetation with terraced path method. This method conducting five paths, each path consisted of 10 plots with 10 m x 100 m which divided into two sub-plots with 5 x 5 m and 10 x 10 m, with total 50 plot (0.5 ha). Data collection consist of diameter and height. The results show that Rhizophora apiculata associated with Rhizophora stylosa at path 1 and 3, however the association type was negative and the association index number categorized as very low. On the other hand, there are some species that not associated with each other but they have a positive association, which founded at path 4 and 5. Path 4 consist of Rhizophora apiculata with Ceriops tagal and path 5 consist of Rhizophora stylosa, Bruguiera gymnorrhiza, and Syzygium polyanthum. Keyword: association, Baluran National Park, mangrove zonation, Rhizophoraceae,